The Relationship Betwen The Use Of Personal Protective Equipment And Work Accidents In Field Workers At PT. PLN (PERSERO) Belawan - anasti, ajeng; Harahap, Reni Agustina (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2024)
Work Unexpected events like work accidents might result in fatalities and property damage. Businesses must supply personal protective equipment to reduce workplace accidents. Workers utilize personal protection equipment (PPE) as a safety measure to shield their bodies from potential workplace risks, illnesses contracted at work, and accidents. The goal of this study is to determine how field workers at PT. PLN (Persero) Belawan's attitude, knowledge, and usage of personal protective equipment relate to work-related accidents. This kind of research uses a cross-sectional study design and is quantitative in nature. There were forty-four samples used. The analysis's findings indicate a significant correlation (Pvalue <0.05) between attitude, knowledge, and the use of personal protective equipment and work accidents in employees at PT. PLN (Persero) Belawan. Attitude (p=0.042), knowledge (p=0.045), and the use of PPE (p=0.034) are the factors that were analyzed. The study concludes that attitudes, knowledge, and the usage of personal protection equipment are related to work-related injuries. In addition to issuing warning letters to employees who do not wear personal protective equipment often, the firm can step up its promotion of the use of PPE, apply penalties and other consequences phrases.